Pulp fiction three stories about one story - Tarantino, Quentin (Faber and Faber, 1999)
Winner of the Academy Award for Best Screenplay and the Palme d'Or at Cannes Film Festival, "Pulp Fiction" exploded onto the screen in 1994 and transformed the direction of contemporary cinema. This triplet of interwoven crime stories displays Tarantino's visceral approach to character and plot.